(3GdMbhb GdSjGSjI ddeQCI aj GdTQjYI GdESdGejI h GdbGfhf GdOIhdj (B/s - (3jMjGhj, CYeQs ((3GdLRGFQ (B:s (3OGQ gheg ddWHGYI h GdfTQ ,s, 2001)
(3bSeJ GdOQGSI Gdi HGHjf jJVef GdGhd GdOaGY Yf GdMbhb GdSjGSjI ddeQCI h gh HOhQg ebSe Gdi aUdjf jJfGhd GdGhd GdeWGdHI HgPg GdMbhb h jJfUH GdKGfj Ydi eYGQVI gPg GdeWGdHI GeG GdHGH GdKGfj ajOhQ Mhd JcQjS GdMbhb GdSjGSjI ddeQCI h eOi JLSjOgG aj GdejOGf h bSefGg Gdi aUdjf fHMK aj GdGhd eVehf gPg GdMbhb h aj GdKGfj eOi GMJQGegG ef GdfGMjI GdJWHjbjI aj GdhGbY GdeYjTjs
(3HHdjhZQGajG (B: (3U(B.171-180s
Keywords: (3GdESdGes; (3GdbGfhf GdOhdjs; (3GdeQCIs; (3GdSjGSIs